The Resilience of an Urban Rail Transit Network: An Evaluation Approach Based on a Weighted Coupled Map Lattice Model - Yuhao Wang; Jie Liu; Zhouyu Li (Mathematics)
Modeling cascading failure in an urban rail transit network (URTN) is essential for evaluating the impact of interruptions and network resilience. Here, a weighted coupled map lattice (CML) model is proposed. This model combines structural network coupling and passenger flow coupling to analyze the cascading failure process triggered by a station failure. Four network performance indicators are developed: network efficiency and subgraph connectivity from the network structure perspective, and OD connectivity and the reciprocal of average transfers from the network service perspective. The resilience of a URTN is measured based on the network performance indicators during station failures. Application of the model to the Wuhan URTN showed that station failure with high numbers of boarding and alighting passengers caused the highest decline in network resilience. The network’s structural resilience was stronger than its service resilience. The relationship between the percentage of failed stations and network performance indicated a significant threshold effect at a 5% failure percentage. Specifically, network performance decreased rapidly when the percentage of failed stations was below 5% and more gradually when it exceeded this threshold. Moreover, network performance exhibited high sensitivity to increases in external perturbation intensity when the failure station percentage was below 5%, but this sensitivity diminished significantly once the percentage surpassed 5%.